2020
DOI: 10.5152/ejbh.2020.5297
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics, Treatment and Outcome of 123 Patients with Synchronous or Metachronous Bilateral Breast Cancer in a Swiss Institutional Retrospective Series

Abstract: European Journal of Breast Health (Eur J Breast Health) is an international, scientific, open access periodical published by independent, unbiased, and double-blinded peer-review principles. It is the official publication of the Turkish Federation of Breast Diseases Societies, and Senologic International Society is the official supporter of the journal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
6
1
Order By: Relevance
“…In the past 13 years, among patients with breast cancer undergoing surgical treatment at the First Medical Center of Chinese PLA General Hospital, 98 were patients with SBBC, and 25 were patients with MBBC, accounting for 1.6% and 0.4% of the breast cancer population, respectively. The incidence of SBBC in this study was significantly higher than that of MBBC, while some studies from Western countries found that the incidence of MBBC was higher than that of SBBC ( 2 , 7 , 17 - 19 ). Some studies have also reported similar incidences of MBBC and SBBC ( 4 , 20 - 22 ).…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In the past 13 years, among patients with breast cancer undergoing surgical treatment at the First Medical Center of Chinese PLA General Hospital, 98 were patients with SBBC, and 25 were patients with MBBC, accounting for 1.6% and 0.4% of the breast cancer population, respectively. The incidence of SBBC in this study was significantly higher than that of MBBC, while some studies from Western countries found that the incidence of MBBC was higher than that of SBBC ( 2 , 7 , 17 - 19 ). Some studies have also reported similar incidences of MBBC and SBBC ( 4 , 20 - 22 ).…”
Section: Discussioncontrasting
confidence: 77%
“…Based on a large population of Surveillance, Epidemiology, and Ends Results (SEER) data, Qiu et al ( 6 ) also showed an interval of 45.62 months. Recently, a study on a Western population reported that the median time interval in patients with MBBC was as long as 111 months ( 7 ). This interval is clearly longer than the time interval of MBBC in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of BBC is slightly higher, 3%, than all BCs. More precisely, synchronous tumors (contemporary bilaterality) represent 0.6%, while those metachronous constitute 2.2% [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…6 Previous studies have reported inconsistent results regarding the prognosis of sBBC and mBBC. Some studies have reported similar outcomes between sBBC and mBBC, 15,18,49 but other studies have reported a poorer survival of patients with mBBC than those with sBBC. 25,39 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%